Incidence of acute hepatitis C in Brazil: temporal trend of cases notified between 2007 and 2018 - Nunes, Karolyne Hellen Braga; Sales, Luiz Henrique Bizinoto; Valente, Olavo Silva; Souto, Francisco José Dutra (Brazilian Journal of Sexually Transmitted Diseases, 2020)
Introduction: With the improvement of biosafety and quality of blood products, hepatitis C virus (HCV) transmission decreased in Brazil. Analyzing temporal trends in the incidence of acute cases may indicate how current HCV circulation is. Objective: To analyze the temporal trend of acute hepatitis C cases from 2007 to 2018. Methods: Analysis of reported cases of acute hepatitis C, using data from the National System of Notifiable Diseases (Sistema Nacional de Agravos de Notificação – SINAN) and the Health Surveillance Department, Ministry of Health. The non-parametric Cusick test was applied to analyze temporal trend. Results: 6,199 cases of acute HCV were reported between 2007 and 2018. The annual incidence rate ranged from 0.17 cases per 100,000 inhabitants in 2007 at 0.28 (2018) (p=0.005). Regarding the age group, the trend of increased notifications was significant in individuals <5 years (p=0.025) and >40 years (p=0.008) of age. Conclusion: Despite the few acute cases reported annually, there has been an increase in recent years, especially in age extremes. Cases in >40 years may mean that some of them are not new, but chronic infections, or because of the growing importance of sexual transmission as a consequence of relaxation in safe sex. Despite possible inconsistencies and weaknesses in the notification systems, these numbers are of concern, justifying efforts to review cases for better classification and clarification of contagion routes.